2013
DOI: 10.1371/journal.pone.0076428
|View full text |Cite
|
Sign up to set email alerts
|

MglA/SspA Complex Interactions Are Modulated by Inorganic Polyphosphate

Abstract: The transcription factors MglA and SspA of Francisella tularensis form a heterodimer complex and interact with the RNA polymerase to regulate the expression of the Francisella pathogenicity island (FPI) genes. These genes are essential for this pathogen’s virulence and survival within host cells. Our goal was to determine if an intracellular metabolite modulate these protein/protein interactions. In this study, we identified inorganic polyphosphate (polyP) as a signal molecule that promotes the interaction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 53 publications
0
16
1
Order By: Relevance
“…Previous work suggested that ppGpp regulates the same set of genes as that regulated by MglA, SspA, and PigR and promotes the interaction between the MglASspA complex and PigR in F. tularensis (21). Another recent study found that polyphosphate binds to the MglA-SspA complex in vitro (33). It could be that ppGpp or polyphosphate interacts directly with the MglA-SspA complex to promote the interaction with PigR and that one or more of the mutants is defective for binding one of these molecules.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous work suggested that ppGpp regulates the same set of genes as that regulated by MglA, SspA, and PigR and promotes the interaction between the MglASspA complex and PigR in F. tularensis (21). Another recent study found that polyphosphate binds to the MglA-SspA complex in vitro (33). It could be that ppGpp or polyphosphate interacts directly with the MglA-SspA complex to promote the interaction with PigR and that one or more of the mutants is defective for binding one of these molecules.…”
Section: Discussionmentioning
confidence: 97%
“…MglA(Y11A), MglA(T47A), MglA(P48S), MglA(Y63A), MglA(R64A), MglA(K101E), SspA (K65E), SspA(V105E), and SspA(L130S) were defective for the interaction with PigR in the E. coli bridge-hybrid assay; therefore, if these substitutions do disrupt binding of another transcription factor, this factor must be conserved in E. coli. The molecules guanosine tetraphosphate (ppGpp) and polyphosphate have been proposed to play a role in virulence gene regulation along with MglA, SspA, and PigR (21,33,34). Previous work suggested that ppGpp regulates the same set of genes as that regulated by MglA, SspA, and PigR and promotes the interaction between the MglASspA complex and PigR in F. tularensis (21).…”
Section: Discussionmentioning
confidence: 99%
“…polyphosphate hexametaphosphate (hexaMP), binds the MglA-SspA complex (Wrench et al 2013b). However, we found that hexaMP did not compete with ppGpp binding to MglA-SspA (Supplemental Fig.…”
Section: Mgla-sspa Interacts Directly and Specifically With Ppgppmentioning
confidence: 99%
“…(p)ppGpp promotes the interaction between PigR and the MglA-SspA complex in E. coli. Prior work suggested that in F. tularensis (p)ppGpp exerts its effects on virulence gene expression by promoting the accumulation of polyphosphate, which in turn, is required for MglA and SspA to form a complex (50). To test whether or not the interaction between MglA and SspA depends (directly or indirectly) on the ability of cells to synthesize (p)ppGpp, we took advantage of a two-hybrid assay we had used previously to detect the interaction between MglA and SspA in E. coli (11,16,51).…”
Section: Resultsmentioning
confidence: 99%
“…Studies in F. tularensis suggest that (p)ppGpp promotes the interaction between PigR and the RNAP-associated MglA-SspA complex (13), and recent work has revealed that ppGpp can bind directly to the MglA-SspA complex to mediate its effects (15). However, other recent findings suggested that (p)ppGpp might exert its effects on virulence gene expression indirectly by promoting the accumulation of polyphosphate, which in turn was required for MglA and SspA to form a complex (50). Here we present evidence that polyphosphate is not required in order for MglA and SspA to interact.…”
mentioning
confidence: 99%